Atomic-Scale Mapping of Impurities in Partially Reduced Hollow TiO2 Nanowires - Lim, Joohyun; Kim, Se-Ho; Armengol, Raquel Aymerich; Kasian, Olga; Choi, Pyuck-Pa; Stephenson, Leigh T.; Gault, Baptiste; Scheu, Christina (Angewandte Chemie International Edition, 2020)
The incorporation of impurities during the chemical synthesis of nanomaterials is usually uncontrolled and rarely reported because of the formidable challenge in measuring trace amounts of often light elements with sub-nanometer spatial resolution. And yet, these foreign elements (introduced by doping, for example) influence functional properties. We demonstrate how the hydrothermal growth and a partial reduction reaction on hollow TiO2 nanowires leads to the introduction of parts per millions of boron, sodium, and nitrogen. This doping explains the presence of oxygen vacancies and reduced Ti states at the surface, which enhance the functional properties of TiO2. Our results were obtained on model metal oxide nanomaterials and they shed light on a general process that leads to the uncontrolled incorporation of trace impurities in TiO2, thereby, having a strong effect on applications in energy-harvesting.
CRIS-Team Scopus Importer:2023-03-07
Keywords: atom probe tomography; electron microscopy; impurities; oxygen vacancies; TiO